(3TQM cfR GdObGjb aj aQhY GdMfajI ddfSajs - (3GdaQGgj GdgQhj, efdG eScjf, eMeO, (B954 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO gh GdhUa HGdLejd GdGNJjGQj ShGA JYdb HGdaVGjd Ch HGdahGVd hGddGe ddLfS hGdeQGOa eWdb GdeSei ef ZjQ Cf jJYQV ddbjOs
(3BNQgG (B:s
(3adeG WQMJ SgGe GdRhL HGdJNGQL Hbj SgeGf ddCe hSge ddYe ajbSe HGbj GdeGd CKdGKG hGdMeO ddg GdPj HfYeJg JJe GdUGdMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 903s
(3cTa GdXfhf (B2 / 1515s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdMfHdjs